Modified Radical Mastectomy (MRM) in Geriatric Patients with Thoracic Epidural Anesthesia (TEA) Technique : A Case Report - Kharisma Saeraya; Faisal Sommeng; Haizah Nurdin (International Medical Journal Corp. Ltd, 2025)
Introduction: Modified Radical Mastectomy (MRM) is one of the main procedures in the management of breast cancer. Thoracic Epidural Anesthesia (TEA) has been known to be an effective technique in delivering superior analgesics and reducing the need for opioids, especially in patients at high risk of general anesthesia. Case: An 80-year-old woman with advanced right breast cancer underwent an MRM procedure using the thoracic epidural anesthesia technique as the primary modality. An epidural catheter is inserted at the T4/T5 interspatial, with the sensory block reaching the clavicle up to three fingers below the mamma line bilaterally. The surgery lasted for 60 minutes without complications, and the patient showed good hemodynamic stability throughout the procedure. Postoperative pain control is obtained with epidural bupivacain infusion and multimodal therapy. The patient was discharged on the fourth postoperative day in a stable condition. Conclusion: TEA is safe and effective for MRM procedures, also in elderly patients. TEA deserves to be considered as an alternative or complementary to general anesthesia in breast surgery, especially in high-risk patient population.